The role of perceived social support on social skills of student with special needs - Iftita Rahmi (Universitas Negeri Yogyakarta, 2021)
The purpose of this study was to discover the relationship between perceived social support from family and peers on the social skills of students with special needs. This study was conducted with postsecondary education students in a 3-year college (N=42) with various types of disability. This study used a quantitative method with a correlational non-experimental approach. The results of this study indicated that perceived social support from family and friends affect the social skills of students with special needs. The form of the social support associated with the social skills of special needs students is emotional and information support. The implications and possible applications of the relationship between social support and social skills among college students with special needs are discussed.